Early development of acute kidney injury is an independent predictor of in-hospital mortality in patients with acute myocardial infarction. Issue 1 (January 2017) - Moriyama, Noriaki; Ishihara, Masaharu; Noguchi, Teruo; Nakanishi, Michio; Arakawa, Tetsuo; Asaumi, Yasuhide; Kumasaka, Leon; Kanaya, Tomoaki; Nagai, Toshiyuki; Fujino, Masashi; Honda, Satoshi; Fujiwara, Reiko; et al.
Abstract: Background: Acute kidney injury (AKI) often occurs in patients with acute myocardial infarction (AMI), and is associated with adverse outcomes. However, it remains unclear how timing of AKI affects it. This study assessed impact of timing of AKI on prognosis after AMI. Methods: This study consisted of 760 patients with AMI who were admitted within 48 h after symptom onset. AKI was diagnosed as increase in creatinine ≥0.3 mg/dl or ≥50% within any 48 h after admission. Patients were classified into 3 groups according to the occurrence and timing of AKI: no-AKI, early-AKI (within 48 h after admission) and late-AKI (>48 h). Early-AKI was classified into transient early-AKI, defined as creatinine returning to the level below the criteria of AKI, and persistent early-AKI. Results: Early-AKI occurred in 64 patients (9%) and late-AKI in 32 patients (4%). Patients with early-AKI had significantly higher mortality (35%) than those with late-AKI (7%, p  < 0.001) and no-AKI (3%, p  < 0.001). Multivariate analysis showed early-AKI was an independent predictor of in-hospital mortality (OR: 3.38, 95% CI: 1.30–8.76, p  = 0.013), but late-AKI was not. Among patients with early-AKI, mortality was significantly higher even if AKI was transient (23%, p  < 0.001). Patients with persistent early-AKI had the highest mortality (66%, p  < 0.001). Conclusions: Early-AKI was associated with worse outcome. Even if renal function once returned to baseline level, patients with early-AKI tended to be at high risk of mortality.